Operations Management: Roles and Duties of Suppliers and Shippers in Supply Chain Management - Liow, Festus Evly R.I.; Indrawati, Raden Ajeng; Latuconsina, Zainuddin; Hasnawati; Faozi, Muhamad Ilham (PT Inovasi Pratama Internasional, 2024)
In order to enhance competitiveness, companies must prioritize product customization, high quality, cost reduction, and distribution speed. To achieve these goals, it is essential to focus on supply chain management. Supply chain management is defined as the integrated process of obtaining materials and services, transforming them into intermediate and final products, and delivering them to customers. This involves activities such as purchasing and outsourcing, in addition to other functions that are crucial for the relationship between suppliers and distributors. The primary objectives of supply chain management (SCM) are the timely delivery of products to consumers, cost reduction, and the improvement of outcomes across the entire supply chain (as opposed to a single company). Additionally, SCM facilitates the reduction of time, the centralization of planning and distribution activities, and the optimization of resources. Given the current circumstances, the application of SCM is particularly advantageous, as it enables the management of the flow of goods or products in a supply chain.